Anesthesia management in a pregnant patient with neurofibromatosis - Çetinkaya Ethemoğlu, Filiz Banu; Gümüş Özcan, İrem (Journal of Surgery and Medicine, 2022)
Neurofibromatosis (NF) is a genetic and multisystemic disease with autosomal dominant transition. It can affect anesthesia applications by affecting more than one system. In the presence of neurofibromas in the airway, it can cause airway obstruction and difficulties in respiratory delivery during general anesthesia. The presence of tumors affecting the central nervous system makes spinal anesthesia risky. Anesthesiologists should act with awareness of each multisystemic complication when evaluating and managing patients. This case report aims to present our general anesthesia practice in an elective cesarean operation in a pregnant patient with neurofibromatosis type 1.